(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the psychological states that influence excessive Internet use and the formation of Internet addiction in adolescence. As a result of the widespread use of Internet technologies, cases of excessive dependence on the virtual environment are increasing among young people. Adolescence is a psychologically sensitive period, during which emotional instability, self-awareness processes, and the need for social relationships increase. Therefore, some psychological factors - a sense of loneliness, anxiety, depressive states, low self-esteem, and stress - appear as important factors in the formation of Internet addiction. The article discusses the relationship of these psychological states with Internet use behavior based on scientific sources.